Final answer:
To find the solutions to the equation y = 2x - 3, substitute different x-values and solve for y.
Step-by-step explanation:
The given equation is y = 2x - 3.
To find the ordered pairs that are solutions to this equation, substitute different x-values and solve for y.
Let's take the first ordered pair (294.5, 61) as an example:
- Plug in x = 294.5 into the equation: y = 2(294.5) - 3
- Simplify: y = 589 - 3 = 586
Therefore, the ordered pair (294.5, 61) is not a solution to the equation y = 2x - 3.
Repeat the same process for the other two ordered pairs to determine if they are solutions to the equation.